Effect of Chronic Administration of Low Dose Rapamycin on Development and Immunity in Young Rats - Lu, Zhenya; Liu, Furong; Chen, Linglin; Zhang, Huadan; Ding, Yuemin; Liu, Jianxiang; Wong, Michael; Zeng, Ling-Hui (PLOS ONE, 2015)
Mammalian target of rapamycin (mTOR) regulates cell growth, cell differentiation and protein synthesis. Rapamycin, an inhibitor of mTOR, has been widely used as an immunosuppressant and anti-cancer drug. Recently, mTOR inhibitors have also been reported to be a potential anti-epileptic drug, which may be effective when used in young patients with genetic epilepsy. Thus, a suitable dose of rapamycin which can maintain the normal function of mTOR and has fewer side effects ideally should be identified. In the present study, we first detected changes in marker proteins of mTOR signaling pathway during development. Then we determined the dose of rapamycin by treating rats of 2 weeks of age with different doses of rapamycin for 3 days and detected its effect on mTOR pathway. Young rats were then treated with a suitable dose of rapamycin for 4 weeks and the effect of rapamycin on mTOR, development and immunity were investigated. We found that the expression of the marker proteins of mTOR pathway was changed during development in brain hippocampus and neocortex. After 3 days of treanent, 0.03 mg/kg rapamycin had no effect on phospho-S6, whereas 0.1, 0.3, 1.0 and 3.0 mg/kg rapamycin inhibited phospho-S6 in a dose-dependent manner. However, only 1.0 mg/kg and 3.0 mg/kg rapamycin inhibited phospho-S6 after 4 weeks treatment of rapamycin. Parallel to this result, rats treated with 0.1 and 0.3 mg/kg rapamycin had no obvious adverse effects, whereas rats treated with 1.0 and 3.0 mg/kg rapamycin showed significant decreases in body, spleen and thymus weight. Additionally, rats treated with 1.0 and 3.0 mg/kg rapamycin exhibited cognitive impairment and anxiety as evident by maze and open field experiments. Furthermore, the content of IL-1β, IL-2, IFN-γ, TNF-α in serum and cerebral cortex were significantly decreased in 1.0 and 3.0 mg/kg rapamycin-treated rats. The expression of DCX was also significantly decreased in 1.0 and 3.0 mg/kg rapamycin-treated rats. However, rats treated with 1.0 mg/ kg rapamycin exhibited fewer and milder side effects than those treated with 3.0 mg/kg. In summary, all these data suggest that there is not a rapamycin dose that can inhibit mTOR for epilepsy without causing any side effects, but 1 mg /kg may be the optimal dose for young rats for suppressing mTOR with relatively few side effects.